A comprehensive model for understanding banking service quality: BANK SERVQUAL. (5th November 2020) - Gupta, Rupali; Kumar, Babita
Paper aims at formulating measure of service quality for banking sector. Study was conducted in three most populated districts of Punjab, India. From each district three public and three private banks having maximum branches were chosen. From each bank, one branch operating in rural and one in urban areas was selected randomly. Hence, total of 36 branches were contacted. In all 720 customers, 20 from each branch (36 * 20 = 720) were surveyed through non disguised structured questionnaire. Findings highlighted that developed model (BANK SERVQUAL) to study service quality is valid and reliable for banking sector. In all 40 variables were considered to find their relative importance to service quality and customer satisfaction. Factor analysis was used to reduce redundant variables and finally six dimensions were identified. The formulated model for measuring service quality of banking sector implies that attitude of customers towards banking services is determined by service quality and customer satisfaction.